Femoral neck system (FNS) versus 4 cannulated compression screws (CCSs) in the treatment of young patients with Pauwels type III femoral neck fracture: a retrospective comparative study - Yang Gao; Tianle Ma; Xiaohu Chang; Peng Jia; Xiaoteng Li; Xin Tang (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aimed to evaluate the clinical effectiveness of the femoral neck system (FNS) compared to four cannulated compression screws (CCSs) for managing Pauwels type III femoral neck fractures in young patients. Methods A retrospective analysis was conducted on young patients with Pauwels type III femoral neck fractures treated at our hospital from January 2021 to December 2022. Patients were categorized into two groups based on their respective internal fixation methods: the FNS group (32 cases) and the CCSs group (41 cases). Various demographic and clinical variables, including age, gender, fracture side, mechanism of injury, Garden classification, and time interval between injury and surgery, were collected. Comparisons were made between the two groups regarding operative duration, intraoperative blood loss, length of hospital stay, hospitalization expenses, time to fracture healing, and Harris hip score at one year post-surgery. Additionally, postoperative complications such as wound infections, nonunion, femoral neck shortening, avascular necrosis of the femoral head, and hardware failure were analyzed. Follow-up duration ranged from 12 to 24 months for all patients. Results There were no significant differences between the FNS and CCSs groups in terms of demographic characteristics, fracture characteristics, time to fracture healing, duration of hospital stay, and Harris hip score at one year post-surgery (p > 0.05). However, the CCSs group exhibited significantly shorter operative time, reduced intraoperative blood loss, and lower hospitalization costs compared to the FNS group (p < 0.05). Patients treated with FNS had longer operative durations (82.33 ± 28.85 min vs. 66.58 ± 14.38 min, p = 0.006), higher blood loss (106.67 ± 65.83 mLvs.70.00 ± 27.39 mL, p < 0.001), and increased hospitalization expenses (58,345.98 ± 3706.57 RMB vs. 35,427.63 ± 3019.30 RMB, p < 0.0001). The incidence of postoperative complications was 21.8% in the FNS group and 26.8% in the CCSs group (p > 0.05), with no significant differences observed in the rates of wound infections, femoral neck shortening, femoral head necrosis, nonunion, and hardware failure between the two groups (p > 0.05). Conclusion In the management of Pauwels type III femoral neck fractures in young patients, FNS demonstrates clinical efficacy comparable to CCSs. However, considering factors such as operative time, intraoperative blood loss, and hospitalization costs, CCSs may be preferred.